Xuebijing Injection Alleviates Pam3CSK4-Induced Inflammatory Response and Protects Mice From Sepsis Caused by Methicillin-Resistant Staphylococcus aureus - Tiantian Li; Yiming Qian; Zhulei Miao; Peiyong Zheng; Ting Shi; Xinru Jiang; Lingyun Pan; Fenghua Qian; Guizhen Yang; Huazhang An; Yuejuan Zheng (Frontiers Media S.A., 2020)
A leading cause of death worldwide is sepsis that develops as a dysregulated immune response to infection. Serious infection caused by methicillin-resistant Staphylococcus aureus (MRSA) increases the difficulty of treatment in septic patients. Host-directed therapy (HDT) is an emerging approach to bacterial infections. Xuebijing injection (XBJ), a commercialized injectable prescription from traditional Chinese medicine, has been used as adjuvant therapy for sepsis with a history of 15 years. Whether it plays a protective role in severe infection caused by antibiotic-resistant bacteria is still unknown. In this study, XBJ significantly improved the survival of MRSA-induced sepsis mice. In MRSA-infected mouse model, XBJ down-regulated the expression of inflammatory cytokines interleukin (IL)-6, tumor necrosis factor (TNF)-α, MCP-1, MIP-2, and IL-10 in sera. Besides that, it decreased the bacterial load in spleens, livers, and alleviated tissue damage of lung, liver, and kidney. The combination of XBJ with vancomycin or dexamethasone exhibited a better down-regulatory role of the inflammatory response. Then, the protective mechanism of XBJ was further investigated. XBJ inhibited heat-killed MRSA-induced IL-6 and TNF-α production in mouse macrophages. XBJ also decreased Pam3CSK4 (a synthetic tripalmitoylated lipopeptide mimicking bacterial lipoproteins)-stimulated expression of IL-6, TNF-α, IL-1β, IL-12, etc. in mouse macrophages. Furthermore, XBJ down-regulated the activation of NF-κB, MAPK, and PI3K/Akt pathways in Pam3CSK4-stimulated mouse macrophages. In conclusion, our findings demonstrated that XBJ played a protective role in MRSA-challenged mice and down-regulated the inflammatory response and the activation of signaling pathways initiated by Pam3CSK4. It enlarged the clinical application of XBJ in the treatment of severe bacterial infection, e.g. caused by MRSA.